Plum lucky - Evanovich, Janet; King, Lorelei (New York : Macmillan Audio, 2008)
Stephanie finds herself in over her head with a caper involving thrice stolen money, a racehorse, a car chase and a bad case of hives--not to mention her grandmother playing the slots in Atlantic City using the stolen money!
Unabridged.
Compact discs.
"A Stephanie Plum between-the-numbers novel"--Container.
Read by Lorelei King.
Keywords: Bounty hunters -- Fiction; Women private investigators -- New Jersey -- Fiction; Plum, Stephanie (Fictitious character) -- Fiction; New Jersey -- Fiction; Audiobooks; Mystery fiction; Humorous fiction